A HISTORIOGRAPHY OF STUDIES ON THE CRISIS OF THE OXUS CIVILIZATION (Proceedings of International Educators Conference, 2023)
This article provides analytical information on the historiography of scientific research on the crisis of the Oxus civilization. Opinions on the influence of nomadic steppe tribes in the crisis of civilization recorded in scientific literature are compared with the results of archaeological field research.